Mission and Martyrdom: A Reappraisal of Mark in African Context. (April 2020) - Oxbrow, Mark
The Greek term mártyras carries the double meaning of witness and martyr. This paper invites an exploration of the relationship between these two concepts in the contexts of first century and contemporary Africa using the life of St Mark as a historical lens. The paper suggests that many Western authored histories of the Christian movement are distorted by a lack of attention to the Eastern and African expansion of the Church in the early centuries and that contemporary African Christians have erroneously bought into this emaciated history and the theology to which it has given rise. Through an examination of various themes in the life, witness and death of St Mark, and the relationship between martyrdom and witness in African Christian history, the paper encourages a reappraisal of the African roots of Christianity as a rich source for contemporary discipleship in Africa and the universal Church.